Growth, Spectral, Optical, Studies of A Zinc Picolinate Dihydrate NLO Single Crystal. (2019) - Chinnasamy, E.; Arulmani, S.; Deepa, K.; Suresh Kumar, D.; Madhavan, J.; Senthil, S.
Abstract: Nonlinear optical material Zinc Picolinate dihydrate (ZPD) was synthesized by slow evaporation solution growth technique. The grown crystals were characterised by Single crystal X-ray diffraction analysis. The presence of functional groups in the grown crystal was analyzed using FT-IR spectrum. The UV-vis spectrum shows a low absorption in the entire visible region. Optical band gap of the grown crystal was found to be 3.98 eV.The evaluation of optical constants by employing UV-visible absorbance data such as, reflectance, extinction coefficient, refractive index, are supportive towards good performance as NLO devices. The nonlinear optical behaviour from the non-centrosymmetric crystal was observed by the generation of frequency doubled (2ω) optical radiation when subjected to pulsed Nd:YAG laser (1064 nm, 10 ns, 10 Hz) using Kurtz-Perry method.